Mechanism of cumulative damage to short fiber type C/SiC under tension. Issue 16 (December 2021) - Tobata, Yuta; Takeuchi, Shinsuke; Goto, Ken
Abstract: Stress–strain relations at different degrees of peak stress were investigated using loading–unloading tests to elucidate cumulative damage mechanisms of short fiber type C/SiC under tension. Damage observations revealed their crack length, number, and angle characteristics. Furthermore, stress–strain relations were estimated by expanding Basista's equations and by substituting measured damage characteristics into them, which revealed a nonlinear stress–strain relation. Cracks propagated in transverse fiber bundles without fiber fracture, connecting other cracks that had 75 ° – 90 ° orientation to the tensile axis. Stress–strain relations estimated qualitatively and quantitatively suggest that mixed mode I and mode II crack opening in transverse fiber bundles in the through-thickness plane caused the stress–strain nonlinear relations.